The Use of Phosphite‐Type Ligands in the Ir‐Catalyzed Asymmetric Hydrogenation of Heterocyclic Compounds. Issue 1 (22nd November 2013) - Lyubimov, Sergey E.; Ozolin, Dmitry V.; Ivanov, Pavel Yu; Melman, Artem; Velezheva, Valeriya S.; Davankov, Vadim A.
ABSTRACT A series of chiral phosphite‐type ligands was tested in asymmetric Ir‐catalyzed hydrogenation of quinolines and 2, 4, 5, 6‐tetrahydro‐1H‐pyrazino(3, 2, 1‐j, k)carbazole. Hydrogenation of quinaldine hydrochloride provided superior enantioselectivity up to 65% ee compared to quinaldine free base. The ligands were tested for the first time in the asymmetric Ir‐Ircatalyzed hydrogenation of 2, 4, 5, 6‐tetrahydro‐1H‐pyrazino(3, 2, 1‐j, k)carbazole yielding the antidepressant drug, pirlindole. Chirality 26:56–60, 2013. © 2013 Wiley Periodicals, Inc.